Travel: a conceptual framework in travel protection plan subscription behaviour among millennials - Nasir, Raihan; Ab Rahman, Asmak (Penerbit UiTM, 2022)
Due to evolving travel trends, safety and security in tourism have become a huge challenge for Malaysians. A series of accidents can drag travelers down to suffer from financial loss; thus, this demands essential coverage for protection during the trip. Despite that, the percentage of Malaysian travellers that subscribe to the Travel Protection Plan (TPP) remains low due to uninsured behaviour caused by a lack of awareness and knowledge, especially among millennials. This paper examines the literature that determines the grounded theories to identify factors that will engage more subscribers towards TPP through content analysis of past consumer behaviour studies. The systematic literature review used in the study shows that past literature has tapped into marketing, performance, sales, product, medical and law implementation areas but scarcely on behaviour areas. The authors proposed that actual behaviour among Millennial travelers can be understood using Decomposed Theory of Behaviour (DTPB) and Risk Perception Theory (RPT), which comprise two factors that influence the subscription behaviour, namely implicit and explicit attitude in TPP subscription. Finally, the article outlined the framework that would construct key strategies from the insight of travellers’ and practitioners’ interviews in line with the proposed theories to understand the actual behaviour of subscription among Millennial travellers. The paper will be useful to researchers, market players and travellers to understand the importance of a Travel Protection Plan subscription before embarking on their journey.